ASURANSI JIWA KREDIT SEBAGAI PERSYARATAN DALAM PENGAJUAN KREDIT PEMILIKAN RUMAH (KPR): Credit Life Insurance as A Requirement for Applying for a Housing Loan (KPR - Putra, Ilham Yugo Adi; Sanusi, Heru Pringgodani (AMICUS CURIAE, 2025)
Home Ownership Credit (KPR) is a financing option offered to prospective residential property buyers. KPR serves as a solution to bridge the gap between home ownership aspirations and the financial capacity of the public. The bancassurance scheme is often combined with life insurance as a guarantee. However, given the long payment duration and various risks that may arise during the credit period, such as the death of the debtor, financial institutions impose credit life insurance requirements as part of the KPR application. This study examines whether credit life insurance is a mandatory requirement in KPR applications. The findings show that banking institutions do require credit life insurance as part of their risk mitigation strategy. This is implemented by Bank Syariah Indonesia, which requires the use of BNI Life Credit life insurance to ensure protection for customers in case of unexpected events such as the death of the debtor. The same can be found at Bank Rakyat Indonesia (BRI), which requires Bringin Life and Heksa Eka Life insurance in KPR applications to mitigate risks. This policy is in line with the Copy of the Financial Services Authority Circular Letter Number 33/SEOJK.03/2016 Concerning the Implementation of Risk Management in Banks Conducting Marketing Cooperation Activities with Insurance Companies (Bancassurance). Thus, the life insurance requirement in KPR is not just a bank preference, but rather an implementation of regulations aimed at maintaining the stability of the banking sector and protecting the interests of all parties involved.